โพรโทคอลไกล่เกลี่ยความผิดพลาดกุญแจรหัสลับด้วยรหัสพาริตีเช็กความหนาแน่นต่ำสำหรับระบบกระจายกุญแจรหัสลับเชิงควอนตัม - ธราธร พรมสะอาด (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
In this thesis, a key reconciliation method is proposed as one of the classical part in Quantum Key Distribution (QKD) protocol. The proposed method aims to correct the transmission error after distribution of quantum key objects over a quantum channel. For error correction, Low-Density Parity-Check (LDPC) codes are adopted as the technique of source coding with side information. This study investigates three main proposed methods covering possible cases of error rates in QKD system. The first method is the LDPC code with bit-flipping and sum product syndrome decoding. This technique deploys a fixed code-rate and achieves an error-correcting performance better than Hamming syndrome in Winnow protocol. Furthermore, the relationship of the decoding methods and block-length effect with reconciliation efficiency is investigated. Secondly, rate-adaptive reconciliation based on LDPC accumulate codes is studied. The sequence accumulate syndrome is stored in a buffer and some elements are sent incrementally to the decoder. Finally, rate adaptive LDPC reconciliation method based on puncturing and shortening technique with estimated Quantum Bit Error Rate (QBER) from only syndrome is studied. This method also estimates reconciliation efficiency in advance for determination of an optimal rate. From numerical results, it can be observed that the performance of our proposed schemes in terms of reconciliation efficiency, a number of disclosed bits and interactive communications is superior to conventional Winnow and Cascade protocols. Therefore, gain of these proposed schemes impacts significantly on the achievable secret key generation rate with responding to the high efficiency for discrete-variable QKD applications.